2020
DOI: 10.1038/s41467-020-16370-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-time terahertz imaging with a single-pixel detector

Abstract: Terahertz (THz) radiation is poised to have an essential role in many imaging applications, from industrial inspections to medical diagnosis. However, commercialization is prevented by impractical and expensive THz instrumentation. Single-pixel cameras have emerged as alternatives to multi-pixel cameras due to reduced costs and superior durability. Here, by optimizing the modulation geometry and post-processing algorithms, we demonstrate the acquisition of a THz-video (32 × 32 pixels at 6 frames-per-second), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
143
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(143 citation statements)
references
References 49 publications
0
143
0
Order By: Relevance
“…[33][34][35][36] At the same time, intensive research has been conducted on THz multipixel cameras and holographic or codedaperture imaging principles. 9,[37][38][39] The main THz spectroscopic approaches that are generally used in biological research are Fourier transform spectroscopy (FTS), photomixing spectrometry, TPS, and TPI. FTS commonly utilizes broadband CW-sources or pulsed sources and the Michelson interferometer scheme, in which the inverse Fourier transform of the recorded interferogram is used.…”
Section: Thz Instrumentationmentioning
confidence: 99%
“…[33][34][35][36] At the same time, intensive research has been conducted on THz multipixel cameras and holographic or codedaperture imaging principles. 9,[37][38][39] The main THz spectroscopic approaches that are generally used in biological research are Fourier transform spectroscopy (FTS), photomixing spectrometry, TPS, and TPI. FTS commonly utilizes broadband CW-sources or pulsed sources and the Michelson interferometer scheme, in which the inverse Fourier transform of the recorded interferogram is used.…”
Section: Thz Instrumentationmentioning
confidence: 99%
“…Considering the difficulty of generating quantum entanglement source, it was proved in theory and experiment that GI could be implemented with thermal and pseudo-thermal light [2][3][4][5][6][7][8] . In recent years, with the proposal of various GI schemes 6,[9][10][11] , GI has a bright application prospect in many related fields, such as remote sensing 12,13 , imaging through scattering media [14][15][16][17] , optical encryption 18,19 and terahertz imaging [20][21][22][23][24] .…”
Section: Improving the Performance Of Ghost Imaging Via Measurement-dmentioning
confidence: 99%
“…Alternatively, our scheme may be generalized to other fields by using elements that convert from optics to the field of interest. For example, it has been demonstrated that illuminating a highly resistive silicon wafer with spatially modulated light can enable the spatial modulation of a terahertz beam transmitted through the wafer 21 . With recent advancements in terahertz SPI, the speed of such systems is currently limited by the rates of DMDs, and thus may be improved by using our scheme.…”
Section: A New Spin On Single-pixel Imaging: Spatial Light Modulationmentioning
confidence: 99%
“…The signal from the detector is recorded for each pattern projected on the object, and the image is formed from the signals by an inversion algorithm. SLM-based SPI has been demonstrated in numerous applications in optics 9 , including visible and infrared microscopy 10 , 3D imaging 11,12 , fluorescence microscopy 13 , multi-spectral imaging 14 , multiphoton wide-field imaging 15 , viewing through scattering media 16 as well as in hybrid optically assisted techniques, such as optoacoustic imaging 17 , optical detection of ultrasound 18 and terahertz imaging [19][20][21] .…”
mentioning
confidence: 99%